2020
DOI: 10.1016/j.impact.2020.100254
|View full text |Cite
|
Sign up to set email alerts
|

The necessity of investigating a freshwater-marine continuum using a mesocosm approach in nanosafety: The case study of TiO2 MNM-based photocatalytic cement

Abstract: Production of Manufactured Nanomaterials (MNMs) has increased extensively due to economic interest in the current years. However, this widespread use raises concern about their impact on human and environment. Current efforts are made, both at national and international levels to help developing safer MNMs in the market. In order to assess hazards of MNMs, it is important to take into account exposome parameters in order to link fate and behavior of MNMs to their potential toxicity. In that context, the aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In addition, the paint matrix prevented (bio)­transformation of the ENMs, with regard to dissolution and complexation. More recently, Châtel et al reported an enhanced bioaccumulation of pristine Ti-ENMs compared to cement-embedded counterparts in freshwater snails …”
Section: Environmental Perspectives and Current Knowledge Gapsmentioning
confidence: 99%
“…In addition, the paint matrix prevented (bio)­transformation of the ENMs, with regard to dissolution and complexation. More recently, Châtel et al reported an enhanced bioaccumulation of pristine Ti-ENMs compared to cement-embedded counterparts in freshwater snails …”
Section: Environmental Perspectives and Current Knowledge Gapsmentioning
confidence: 99%
“…However, they have different shell morphology and P. corneus presents a deeper and longer diving behaviour compared with L. stagnalis (Bekius, 1971). Moreover, these species are considered good environmental pollution indicators given their wide geographic distribution, ease of availability, and sensitivity toward chemicals (Amorim et al, 2019;Châtel et al, 2020;Herbert et al, 2021). The L. stagnalis has been used as an excellent biological model for ecotoxicological studies and is applied in OECD test guidelines (Amorim et al, 2019;Ducrot et al, 2014).…”
Section: Introductionmentioning
confidence: 99%